2024
DOI: 10.1101/2024.01.18.576285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PINK1 knockout rats show premotor cognitive deficits measured through a complex maze

Isabel Soto,
Vicki A. Nejtek,
David P. Siderovski
et al.

Abstract: Cognitive decline in Parkinsons disease (PD) emerges up to 10 years before clinical recognition. Neurobiological mechanisms underlying premotor cognitive impairment in PD can potentially be examined in the PINK1 / rat, which exhibits a protracted motor onset. To enhance translation to human PD cognitive assessments, we tested a modified multiple T-maze, which measures cognitive flexibility similarly to the Trail-Making Test in humans. Like human PD outcomes, PINK1-/- rats made more errors and took longer to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…al, 2022; Kelm-Nelson et al, 2021; Creed et. al, 2019; Villeneuve et al, 2016; Cai et al, 2019; Hoffmeister et al, 2020; Grant et al, 2015; Cullen et al, 2018; Lechner et al, 2022; Soto et al, 2024). Accordingly, this highlights the apparent complexities related to PINK1 function and its influence on nigrostriatal neurodegeneration and DA regulation (Urrutia, 2014).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…al, 2022; Kelm-Nelson et al, 2021; Creed et. al, 2019; Villeneuve et al, 2016; Cai et al, 2019; Hoffmeister et al, 2020; Grant et al, 2015; Cullen et al, 2018; Lechner et al, 2022; Soto et al, 2024). Accordingly, this highlights the apparent complexities related to PINK1 function and its influence on nigrostriatal neurodegeneration and DA regulation (Urrutia, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Yet, two studies investigating cognitive functioning in this model have failed to note any significant deficits (Cai et al, 2019; Ferris et al, 2018). Nonetheless, the similar NOR scores may be attributed, at least in the younger cohorts, to the task’s inability to capture subtle changes in executive functioning, the domain of cognition initially impacted in PD (Ferris et al, 2018; Dirnberger et al, 2013; Aarsland et al, 2017; Nejtek et al, 2021; Soto et al, 2024). F-FDOPA PET scans have suggested that elevated dopaminergic activity in the PFC and constitutes a pathological feature of early-stage PD (Bruck et al, 2005; Kaasinen et al, 2001; Fallon et al, 2012), which is in alignment with our DA results in PFC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation